F13 Progressive reduction of plasma 24S-hydroxycholestrol in prodromal HD subjects according with clinical and MRI features in the PREDICT-HD study. (29th August 2012) - Valerio, L; Di Donato, S; Long, J; Juhl, A; Paulsen, J
Abstract : Background: Significantly reduced plasma 24OHC was found in HD patients compared with healthy subjects. The reduction of plasma 24OHC parallelled the shrinking of caudate volumes at MRI, suggesting that the observed reduction of plasma 24OHC might reflect the progressive loss of metabolically active neurons in the grey matter. In a small group of prodromal subjects, plasma concentration of 24OHC was similar to controls. However, the subjects closer to motor onset and with smaller striatum presented lower levels of 24OHC, similar to the concentrations of the HD patients (Leoni et al, 2008). Methods: By isotope dilution Mass Spectrometry we measured plasma 24OHC in 30 Controls individuals, 90 pre manifest gene positive for HD individuals (Far from Onset (Far, n=21), mid term form onset (Mid, n=36), Near to Onset (Near, n=33), and in 30 gene clinically manifesting individuals (manifest HD) from the PREDICT-HD project. Results: The levels of 24OHC in plasma were significantly reduced in the clinically manifest patients compared to Controls (ANOVA, p<0.001) and compared to the Far group (p<0.001). No significant differences were found between Near and manifest individuals, as well no significant differences were found between Controls and Far individuals. Both Controls and Far from onset groups were significantly higher compared to Near individuals (<0.001). The individuals described as Mid have slightly but not significantly lower levels compared to Controls and Far from onset individuals, while higher compared to Near to onset (NS) and clinically manifest individuals (0.003). Levels of 24OHC were significantly correlated to disease burden with a significant trend towards reduction along the progression of the disease. Statistically significant correlations were also found between plasma 24OHC and MRI, and 24OHC selected and functional, motorial and psychological parameters.